Analisis Hukum Terhadap Kewenangan Otoritas Jasa Keuangan Dan Kementerian Koperasi dan Usaha Kecil dan Menengah Dalam Pengawasan Lembaga Keuangan Mikro Berbentuk Koperasi - Diah Ayu Oktriningsih; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. Indonesian’s economic development are keep growing and it made various regulatory agencies which have authorization to supervise a financial institution. Financial Services Authority (Otoritas Jasa Keuangan as known as OJK) exist as the institution which have the authority to regulate, supervise, and investigate a financial institution. The main issue for this research is about the authority of OJK in supervising Micro Financial Institution (Lembaga Keuangan Mikro as known as LKM) of Cooperation, meanwhile cooperation legal entity scouted and supervised by Ministry of Cooperation and Small and Medium Enterprises. This research is normative legal research through library research and field research and also through study of document as the data collection technique. The Data analysis is by using qualitative method of analysis. The data used in this research is secondary data source with primary legal material, they are: Law number 25 of 1992 about Regulation of Cooperation, Law number 21 of 2011 about Financial Service Authority, and Law number 1 of 2013 about Micro Financial Institution. The result of the research can be known that OJK under the Law number 21 of 2011 about Financial Service Authority has the functions, duties, and authority of arrangement, supervision, inspection, and investigation of financial institution. OJK supervising LKM of Cooperation based on attribution authority and as Lex specialist based on Law number 1 of 2013 about Micro Financial Institution and on the implementation referred to Regulation of Financial Services Authority number 14/POJK.05/2014 about The Development and Supervision of Micro Financial Institution. Ministry of Cooperation and Small and Medium Enterprises is not supervising LKM of Cooperation and only carrying the affirmation of Cooperation itself as the legal entity. Business activities of LKM are fully  the authority of OJK in granting business license, coaching, supervising, and inspection and financial investigation. The authority of OJK in supervising LKM of Cooperation is not against Law number 25 of 1992 about Regulation of Cooperation and Ministry of Cooperation and Small and Medium Enterprises Regulation number 17/Per/M.KUKM/IX/2015 about Supervising Cooperation and or with other legislation about Cooperation.   Keywords: OJK, Financial Services Authority, Small and Medium Enterprises, Micro Financial Institution,